Translanguaging In Indonesian EFL Classrooms: A Comparative Case Study Of Pedagogical Strategies And Linguistic Identity - Yasyinta Nindy Yolandana, Ika; Endang Setyaningsih, Endang; Arifah Drajati, Nur (CV. Inara, 2024)
The convergence of language and education is crucial for achieving academic achievement in a world that is becoming more and more multilingual. The present study aims to investigate the impact of translanguaging on the positive perception of English as a Foreign Language (EFL) abilities, academic engagement, and comprehension among university students in Indonesia. This study investigates the impact of translanguaging on students' perceptions of their linguistic competence in English as a Foreign Language (EFL) settings. It utilizes qualitative analysis of in-depth interviews with three EFL learners, namely Dewi, Dina, and Dewa. Additionally, the study explores how translanguaging practices contribute to the creation of inclusive and engaging classroom environments that cater to diverse linguistic backgrounds. Dewi, an advanced English as a Foreign Language (EFL) student, proposes a 75% utilization of English to enhance the development of linguistic skills. Conversely, Dewa favors a 25% utilization rate, giving priority to Indonesian to enhance conceptual understanding for learners at an intermediate level. Dina, an individual who is new to the subject, advocates for a balanced strategy that ensures equal exposure to both languages. The diverse tastes highlight the necessity for flexible teaching methods that may effectively address the multilingual environment of Indonesian education. The results indicate that translanguaging not only strengthens students' favorable self-perceptions and academic engagement but also improves understanding of intricate topics. Furthermore, the research sheds light on the potential of translanguaging as a pedagogical instrument that educators can utilize to establish learning environments that are both inclusive and efficacious. By strategically incorporating language, educators can acknowledge and make use of students' linguistic abilities, thus validating their identities and fostering a favorable attitude towards multilingualism. The research supports the adoption of an educational framework that not only facilitates but also acknowledges linguistic diversity, suggesting that this approach is crucial for academic progress in multilingual environments.